Alien separation - Koch, Gini (Koch, Gini. Alien novels., 2015)
Before Jeff and Kitty Katt-Martini can take down the Mastermind, they are transported to another solar system and into the middle of the Alpha Centauri system's Civil War where they must fight a battle that isn't their own to get home and stop their enemy from destroying Earth and everyone they love.